2008
DOI: 10.1002/jcp.21630
|View full text |Cite
|
Sign up to set email alerts
|

Subnuclear targeting of the Runx3 tumor suppressor and its epigenetic association with mitotic chromosomes

Abstract: Runx proteins are tissue-specific transcriptional scaffolds that organize and assemble regulatory complexes at strategic sites of target gene promoters and at intranuclear foci to govern activation or repression. During interphase, fidelity of intranuclear targeting supports the biological activity of Runx1 and Runx2 proteins. Both factors regulate genes involved in cell cycle control and cell growth (e.g., rRNA genes), as well as lineage commitment. Here, we have examined the subcellular regulatory properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…Nuclear exclusion of RUNX proteins can be accommodated by decreasing microtubule-dependent nuclear import, reducing nuclear retention by loss of association with chromatin-related macromolecular complexes or inhibiting nuclear export (Pockwinse et al, 2006;Pande et al, 2009). Moreover, activation of TGF-b pathway triggered nuclear translocation of endogenous RUNX3 in SNU16 cells and this subsequently led to growth inhibition .…”
Section: Mechanisms Underlying Cytoplasmic Translocation Of Runx3mentioning
confidence: 99%
“…Nuclear exclusion of RUNX proteins can be accommodated by decreasing microtubule-dependent nuclear import, reducing nuclear retention by loss of association with chromatin-related macromolecular complexes or inhibiting nuclear export (Pockwinse et al, 2006;Pande et al, 2009). Moreover, activation of TGF-b pathway triggered nuclear translocation of endogenous RUNX3 in SNU16 cells and this subsequently led to growth inhibition .…”
Section: Mechanisms Underlying Cytoplasmic Translocation Of Runx3mentioning
confidence: 99%
“…Mutation or dysregulation of RUNX genes have been associated with diverse cancer types (3). Unlike many transcription factors (e.g., Ets-1 and Oct-1) (4), RUNX proteins are retained at the condensed mitotic chromatin, where they maintain epigenetic memory and ensure proper transmission of gene expression patterns to progeny cells; RUNX2 binds to the promoters of various cell cycle-and cell fate-related genes and regulates histone modifications during mitosis (5); RUNX2 and RUNX3 bind to regulatory regions of rRNA genes and are associated with their repression (6,7). RUNX1 positively regulates the transcription of various spindle assembly checkpoint genes, such as BUB1 and NEK6 (8).…”
mentioning
confidence: 99%
“…In 2003, our group identified the osteogenic master regulator RUNX2 as the first sequence specific bookmark that remained associated with target genes through mitosis (Zaidi et al 2003). Subsequent studies of RUNX family of phenotypic transcription factors from our group (Zaidi et al 2003;Young et al 2007a;Young et al 2007b;Ali et al 2008;Bakshi et al 2008;Pande et al 2009;Ali et al 2010;Zaidi et al 2010;Ali et al 2012;Zaidi et al 2014;Lopez-Camacho et al 2014) and studies by other groups examining various transcription factors (Xing 2005;Sarge and Park-Sarge 2005;Dey et al 2009;Blobel et al 2009;Zhao et al 2011;Kadauke et al 2012;Arampatzi et al 2013;Caravaca et al 2013;Kadauke and Blobel 2013;Lake et al 2014;Zaret 2014;Lodhi et al 2014;Wong et al 2014;Lodhi et al 2016;Lerner et al 2016;Festuccia et al 2016) have identified mitotic bookmarking as a key epigenetic mechanism for regulation of genes that coordinate cell growth and lineage maintenance following mitosis.…”
Section: Mitotic Bookmarking: a Historical Perspectivementioning
confidence: 89%
“…Ali et al 2008;Bakshi et al 2008;Pande et al 2009;Dey et al 2009;Blobel et al 2009;Ali et al 2010;Zaidi et al 2010;Zhao et al 2011;Ali et al 2012;Kadauke et al 2012;Arampatzi et al 2013;Caravaca et al 2013;Kadauke and Blobel 2013;Zaidi et al 2014;Lake et al 2014;Zaret 2014;Lodhi et al 2014;Wong et al 2014;Lopez-Camacho et al 2014;Lodhi et al 2016;Lerner et al 2016;Festuccia et al 2016). Each of these transcription factors occupy a subset of their target genes during mitosis in their respective lineages.…”
Section: Properties Of Transcription Factors That Function As Mitoticmentioning
confidence: 99%